Linguistic "purity", morphological borrowings and issues of cross-cultural communication - Amatov, Alexander Mikhailovich; Sedykh, Arkadiy Petrovich; Yanutik, Stella Yanovna; Filimonova, Naralia Gennadievna; Buzinova, Lyudmila Mikhailovna; Pashkovskaia, Natalia Dmitrievna (Universidade Estadual Paulista, 2021)
The article deals with several aspects of language regulation considering social, economic, and political factors as well as their reflection in amateur and academic dictionaries of the English and French languages. It is shown that although the issues of language "purity" have been raised over several centuries, the approaches to the solution of these issues in different countries vary significantly. These differences are primarily associated with the status of the language in the globalizing world of today. Consequently, there is a broad spectrum of political, economic, and social factors that set in motion the various mechanisms of language regulation – from purely scientific interest or laments over the "beauty of the original language" to issues of adequate functioning and, ultimately, the survival of national languages.